2016
DOI: 10.1007/s00477-016-1212-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and visualizing uncertainties of flood boundary delineation: algorithm for slope and DEM resolution dependencies of 1D hydraulic models

Abstract: As flood inundation risk maps have become a central piece of information for both urban and risk management planning, also a need to assess the accuracies and uncertainties of these maps has emerged. Most maps show the inundation boundaries as crisp lines on visually appealing maps, whereby many planners and decision makers, among others, automatically believe the boundaries are both accurate and reliable. However, as this study shows, probably all such maps, even those that are based on high-resolution digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…To evaluate the applicability of the disparity-distance equation and algorithm by Brandt (2016) in deriving uncertainty boundaries that account for both the DEM resolution and the slope characteristics of the area, Lim's (2011) earlier modelling results for a part of the Testebo River (i.e. Forsby and Varva), north of Gävle, Sweden, were utilised as test cases.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the applicability of the disparity-distance equation and algorithm by Brandt (2016) in deriving uncertainty boundaries that account for both the DEM resolution and the slope characteristics of the area, Lim's (2011) earlier modelling results for a part of the Testebo River (i.e. Forsby and Varva), north of Gävle, Sweden, were utilised as test cases.…”
Section: Methodsmentioning
confidence: 99%
“…Brandt, 2016) concluded that DEMs of between 4 and 10 m resolution (or point spacing) are enough to model flood boundaries with sufficient accuracy (e.g., Werner, 2001;Casas et al, 2006;Raber et al, 2007). However, those recommendations are based on the total characteristics of the model results; i.e.…”
Section: Dem-related Uncertaintiesmentioning
confidence: 99%
See 3 more Smart Citations